PENGARUH EDUKASI EARLY WARNING SYSTEM (EWS) TERHADAP RESPON TIME PERAWAT DI IGD BRSUD KABUPATEN TABANAN - Budiari, Ni Made; Susila, I Made Dwie Pradnya; Arisudhana, Gede Arya Bagus (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Emergency patient care is a service that requires immediate service, namely fast, precise, and accurate to prevent death or disability. One of the indicators of service quality is in the form of response time, which is a process indicator to achieve the outcome indicator, namely survival. To achieve a fast response time, a systematic approach system is needed in dealing with patients who experience emergencies, one of which is by using the Early Warning System (EWS). This study aims to determine the effect of early warning system education on the response time of nurses in Emergency Room Tabanan Hospital. This study used an experimental method with a pre-experimental design (one-group pre-test-posttest design) involving 39 samples selected by total sampling technique. Data collection in providing EWS education is in the form of modules, and the research material is in the form of a clock used to measure the response time. Data analysis uses a computerized system with univariate and bivariate analysis. This study showed that the response time for nurses before the early warning system education was fast, namely 15 (39.5%). Most of the nurses' response time after the early warning system education was 26 (66.7%). The results of this study can be concluded that there is an effect of early warning system nurse education on the response time of nurses with a significance value (p) of 0.000.